Short-term Outcomes of Intracorporeal Versus Extracorporeal Totally Stapled Anastomosis after Laparoscopic Colectomy: A Propensity Score-matched Cohort Study - Yoshiaki Fujii; Kenji Kobayashi; Hirozumi Sawai; Seiya Yamamoto; Shuhei Uehara; Hirotaka Miyai; Hiroki Takahashi; Shuji Takiguchi (Journal of the Anus, Rectum and Colon)
Objectives: To describe detailed surgical techniques for totally stapled intracorporeal anastomosis (TSIA) and determine their feasibility and safety by comparing short-term outcomes with those of conventional totally stapled extracorporeal anastomosis (TSEA). Methods: In total, 59 consecutive patients who underwent laparoscopic colectomy between June 2018 and August 2021 were retrospectively assessed. Linear staplers were used for all anastomoses. The TSIA and TSEA groups included 23 and 36 patients, respectively. Following a comprehensive description of each surgical technique, propensity score matching analysis was conducted to compare matched groups on the basis of clinicopathological characteristics, surgical and perioperative outcomes, complications, and postoperative inflammatory reactions. After matching, 17 cases each were analyzed in the TSIA and TSEA groups. Results: Both groups were well matched. The TSIA group had significantly lesser blood loss than did the TSEA group (10 versus 20 mL, p=0.002), although this result was not clinically significant. The skin excision length (4 versus 6 cm, p<0.001) and postoperative hospital stay length (6 versus 7 days, p<0.001) were significantly shorter in the TSIA group than in the TSEA group. Increasing C-reactive protein (CRP) values at 1, 3, and 6 postoperative days were significantly lower in the TSIA group than in the TSEA group (p=0.016, p=0.011, and p=0.012, respectively). Conclusions: TSIA is a simple, feasible, and efficient surgical technique; compared with TSEA, it is less invasive and associated with lesser blood loss, shorter skin incision lengths, shorter postoperative hospital stays, and lower CRP level increases.